STATISTICAL METHODS OF ANALYSIS OF FINANCIAL INDICATORS NEEDED TO MODEL VALUATIONS - Ivan E. Akulin (Статистика и экономика, 2016)
The article presents the methods of analysis and interpretation of financial performance required to create a comprehensive and universal model of valuation. The author provides an alternative method of smoothing, the concept of «sliding smoothed annualized income» as a new unit for analysis. The concept «value sales» and variants of use this indicator are given.